Editors and Guidelines of the TAWARIKH Journal, Issue of October 2017 - TAWARIKH, Editor Journal (ASPENSI in Bandung, Indonesia, 2017)
TAWARIKH:Â International Journal for Historical Studies.Â Â This journal, with ISSN 2085-0980, was firstly published on 28 October 2009, in the context to commemorate the Youth Pledge Day in Indonesia. Since issues of April 2016 to date, the TAWARIKH journal has been organized by the Lecturers at the Faculty of Adab and Humanities UIN (State Islamic University) Sunan Gunung Djati in Bandung; and published by Minda Masagi Press as a publishing house owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every October and April. For period 2012 to 2017, the TAWARIKH journal has been accredited by Ditjendikti Kemdikbud RI (Directorate-General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia).Bandung, Indonesia: October 30, 2017.Prof. Dr. Haji SulasmanEditor-in-Chief of TAWARIKH Journal; and Senior Lecturer at the Department of Islamic Civilization History FAH UIN SGD in Bandung, West Java, Indonesia.